2013
DOI: 10.1007/s13277-013-0678-2
|View full text |Cite
|
Sign up to set email alerts
|

P53 codon 72 Arg/Pro polymorphism and lung cancer risk in Asians: an updated meta-analysis

Abstract: The polymorphism of p53 codon 72, a transversion of G to C (Arg to Pro), has been demonstrated to be associated with the risk for lung cancer. However, individual studies conducted in Asians have provided conflicting and inconclusive findings. Thus, we performed a meta-analysis by pooling all currently available case–control studies to estimate the effect of p53 codon 72 Arg/Pro polymorphism on the development of lung cancer. The pooled odds ratios (ORs) with the corresponding 95 % confidence intervals (95 %CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…In a metaanalysis of 51 studies, polymorphism TP53 Arg72Pro (rs1042522) was significantly associated with lung cancer risk in any genetic model (Ye et al, 2014). According to S. Wang et al (2013), the Arg72Pro genotype positively correlated with lung cancer risk in Asians. Only few studies attempted to determine the impact of polymorphism TP53 Arg72Pro (rs1042522) on cancer risk in the Kazakh population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a metaanalysis of 51 studies, polymorphism TP53 Arg72Pro (rs1042522) was significantly associated with lung cancer risk in any genetic model (Ye et al, 2014). According to S. Wang et al (2013), the Arg72Pro genotype positively correlated with lung cancer risk in Asians. Only few studies attempted to determine the impact of polymorphism TP53 Arg72Pro (rs1042522) on cancer risk in the Kazakh population.…”
Section: Discussionmentioning
confidence: 99%
“…The published data on the association between polymor phism TP53 Arg72Pro (rs1042522) and lung cancer risk in Asians remain controversial (Wang et al, 2013). Zhao et al (2018) have shown that the Pro72Pro genotype is associated with a higher risk of cancer due to poorer ability to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…They found no significant association between p53 Codon 72 Arg/Pro polymorphism and risk of oral cancer ( 19 ). Wang et al performed a meta-analysis by pooling 14 publications and suggested that the p53 Codon 72 Arg/Pro polymorphism is a risk factor for lung cancer in the Asian population( 20 ). Zhou et al performed a meta-analysis by pooling 12 publications and suggested that the p53 Codon 72 polymorphism may be associated with gastric cancer among Asians, and they further indicated that difference in genotype distribution may be associated with the location, stage, and histological differentiation of gastric cancer( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Survival of lung cancer patients undergoing lung resection was more than 80%, which suggested that early detection and diagnosis helped immensely in the early treatment of lung cancer. 7 , 8 Increasing evidence has indicated that polymorphisms of numerous susceptible genes play a significant association in the development of lung cancer. Thus, these polymorphisms could be useful as biomarkers for lung cancer detection.…”
Section: Introductionmentioning
confidence: 99%